2015
DOI: 10.1038/srep08585
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency magnetic fields do not aggravate disease in mouse models of Alzheimer's disease and amyotrophic lateral sclerosis

Abstract: Low-frequency magnetic fields (LF-MF) generated by power lines represent a potential environmental health risk and are classified as possibly carcinogenic by the World Health Organization. Epidemiological studies indicate that LF-MF might propagate neurodegenerative diseases like Alzheimer's disease (AD) or amyotrophic lateral sclerosis (ALS). We conducted a comprehensive analysis to determine whether long-term exposure to LF-MF (50 Hz, 1 mT) interferes with disease development in established mouse models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
(56 reference statements)
0
5
0
1
Order By: Relevance
“…An in vitro ALS model reported that magnetic field exposure caused impairment of iron homeostasis in SOD-1 mutant cells through deregulation of expression of iron-related genes, recently suggested as molecular determinant in the pathogenesis of ALS 46 . However, in mouse models expressing mutant Cu/Zn-superoxide dismutase, low-frequency magnetic field exposure did not alter disease onset and survival 47 . Another report implementing a SOD-1 transgenic mouse model did not reveal any effect on survival between exposed and unexposed groups.…”
Section: Discussionmentioning
confidence: 83%
“…An in vitro ALS model reported that magnetic field exposure caused impairment of iron homeostasis in SOD-1 mutant cells through deregulation of expression of iron-related genes, recently suggested as molecular determinant in the pathogenesis of ALS 46 . However, in mouse models expressing mutant Cu/Zn-superoxide dismutase, low-frequency magnetic field exposure did not alter disease onset and survival 47 . Another report implementing a SOD-1 transgenic mouse model did not reveal any effect on survival between exposed and unexposed groups.…”
Section: Discussionmentioning
confidence: 83%
“…However, a recent report suggests that long-term exposure (18 months) to ELF-MF (50 Hz, 1 mT) has no effect on the cellular processes involved in the pathogenesis of AD (Liebl et al, 2015). Only few in vivo studies are available to support this theory; most recent studies such as Liebl et al (2016) (Liebl et al, 2015) (the first comprehensive study on the association of ELF-MF with AD in mouse models) or Maes et al (2016) (Maes et al, 2016) suggested that further investigations are needed. In general, experimental findings are based on short-term exposure to very high ELF-MF (typically ≥1 mT) and these studies do not represent realistic occupational exposure scenarios (long-term at lower levels).…”
Section: Discussionmentioning
confidence: 99%
“…The main theoretical premise behind this hypothesis is that exposure to ELF-MF can promote inflammation processes and thus influence the progression of neurodegenerative diseases including AD (Galasko and Montine, 2010;Grammas, 2011). However, a recent report suggests that long-term exposure (18 months) to ELF-MF (50 Hz, 1 mT) has no effect on the cellular processes involved in the pathogenesis of AD (Liebl et al, 2015). Only few in vivo studies are available to support this theory; most recent studies such as Liebl et al (2016) (Liebl et al, 2015) (the first comprehensive study on the association of ELF-MF with AD in mouse models) or Maes et al (2016) (Maes et al, 2016) suggested that further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 900 MHz GSM fields caused only modest increases in constitutive HSP70 and HSP90 expression and concomitantly decreased α‐synuclein expression, all of which were attributable to a 0.5 °C increase in temperature [Terro et al, ]. Recent reports using long‐term ELF EMF exposures suggest these did not aggravate disease in mouse models of Alzheimer's or amyotrophic lateral sclerosis [Liebl et al, ], and improved both spatial memory disorder and hippocampal damage in a rat model of Alzheimer's [Liu et al, ]. Further studies of EMF effects in tractable models of human neurodegenerative diseases are urgently needed, and any robust effects reported will require exact replication by several independent laboratories.…”
Section: Discussionmentioning
confidence: 99%